Teachergrams: A New Trend of Teaching and Learning English - Herman Resyadi (Institut Agama Islam Negeri Palopo, 2020)
This paper focused on exploring the teachergrams phenomenon and English language learning. Thus, this paper outlined two main points including the the teachergrams existence in Instagram and their roles in English language learning. The result discussed showed that teachergrams have ability to turn instagram into interactive learning tool in English language learning. The discussion concludes that the existence of teachergrams have become a useful tool to spread English materials and contents for the followers/English learners in Instagram. Additionally, the content written in this paper is expected to be valuable resources for the people who teach and learn English in digital platform especially Instagram.